Analysis in a large hyperkalemic periodic paralysis pedigree supports tight linkage to a sodium channel locus. - Ptacek, L J (1991)
Hyperkalemic periodic paralysis (HYPP) is an autosomal dominant muscle disease with electrophysiological abnormalities suggesting a defect in a voltage-gated sodium channel (NaCh) gene. A human NaCh gene was recently shown to cosegregate with the disease allele in a family with HYPP. Using an independent clone, we have demonstrated close genetic linkage between an NaCh gene and the HYPP locus in another family. With physiological data demonstrating abnormal NaCh function in HYPP patients, the absence of any obligate recombinations in the two families strengthens the argument that this NaCh gene is the site of the defect in this disorder.